2018
DOI: 10.1111/cas.13882
|View full text |Cite
|
Sign up to set email alerts
|

Coupling function of cyclin‐dependent kinase 2 and Septin2 in the promotion of hepatocellular carcinoma

Abstract: Hepatocellular carcinoma (HCC) is a common and aggressive malignant tumor with a poorly defined molecular mechanism. Cyclin‐dependent kinase 2 (CDK2) and Septin2 (SEPT2) are 2 known oncogenic molecules but the mechanism of functional interactions remains unclear. Here, we interestingly found that CDK2 and SEPT2 show very similar dynamic expression during the cell cycle. Both CDK2 and SEPT2 show the highest protein levels in the G2/M phase, resulting in CDK2 interacting with SEPT2 and stabilizing SEPT2 in HCC. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…Septin 7 plays a downstream effect in ERK3-induced migration of cancer cells, and its deletion abolishes the ability of ERK3 to promote lung cancer cell migration and invasion [47]. CDK2 interacts with SEPT2 to stabilize SEPT2 in HCC cells, and HCC with high expression of both CDK2 and SEPT2 is more prone to recurrence and may be more aggressive [48]. As a new member of the septin family, we reported the function of SEPT11 in HCC progression for the first time.…”
Section: Discussionmentioning
confidence: 90%
“…Septin 7 plays a downstream effect in ERK3-induced migration of cancer cells, and its deletion abolishes the ability of ERK3 to promote lung cancer cell migration and invasion [47]. CDK2 interacts with SEPT2 to stabilize SEPT2 in HCC cells, and HCC with high expression of both CDK2 and SEPT2 is more prone to recurrence and may be more aggressive [48]. As a new member of the septin family, we reported the function of SEPT11 in HCC progression for the first time.…”
Section: Discussionmentioning
confidence: 90%
“…SEPT2 and its family members are important oncogenes that play roles in the development of various tumours (Bridges and Gladfelter, 2015). For example, high expression of SEPT2 was significantly correlated with tumour differentiation and microvessel infiltration, which was an independent prognostic factor in patients with HCC (Xu et al, 2019). SEPT2 and SEPT9 suppression inhibited glioblastoma cell proliferation, caused S phase cell cycle arrest in a coordinating mechanism, decreased cell invasion and significantly inhibited glioma xenograft growth in nude mice (Xu et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…SEPT2 is crucial in spindle formation and sister chromatid separation, thereby regulating G2/M phase transition and cell mitosis [ 19 ]. Whereas several studies have shown that SEPT2 can facilitate tumor growth and metastasis [ 20 , 21 ]. We identified that the two crotonylation sites in SEPT2, K318 (H/L = 1.3, p < 0.05) and K74 (H/L = 2.19, p < 0.05), were significantly differentially crotonylated, as determined by LS-MS/MS.…”
Section: Resultsmentioning
confidence: 99%